PENGARUH PERLAKUAN TAWA TERHADAP TEKANAN DARAH PADA LANSIA YANG HIPERTENSI DI WILAYAH KERJA PUSKESMAS SUMBERSARI KABUPATEN JEMBER - Nuning Dwi Merina (Jurnal Kesehatan dr. Soebandi, 2013)
Almost eldery have high blood pressure. The increase of artheriosclerosis and cortisol for eldery could be a condition that called hypertension. Sumbersari Public Health Center is one of region that have high value of hypertension and also eldery. A solution for handling this problem is laugh treatment. Laugh treatment could decrease cortisol and less the activity of symphatic. This research use time series-control design with 32 sampel and need time 4 weeks to finish this laugh treatment. The result of this research are thre is a different between blood pressure before and after laugh exercise. There is also a differences between blood pressure respondens that given and not given laugh exercise for a month. The manifestation of this result is p value for dependent and independent is p=0,001. It can be concluded that there are significant effect of laugh treatment in decrease of blood pressure in eldery with hypertension. Further studies should involve larger respondens,longer time, and better measurement tools to obtain more accurate result.